Magnetoelektriki - Blinc, Robert (Obzornik za matematiko in fiziko, 2008)
Some properties of magnetoelectric systems are reviewed. These systems show simultaneously ferromagnetic and ferroelectric properties. Though magnetic systems are known since ancient times and ferroelectrics are known for nearly hundred years, intensive research of magnetoelectric systems started only recently. This is so in spite of the fact that Pierre Curie in 1894 predicted the existence of such systems on the basis of symmetry considerations. The renewed interest in magnetoelectric systems is due to their possible applications in memories and spintronics.
Keywords: feroelektriki; feromagnetiki; magnetoelektriki